ATPase and multidrug transport activities of the overexpressed yeast ABC protein Yor1p - Decottignies, A; Grant, A; Nichols, J; De Wet, H; McIntosh, D; Goffeau, A (American Society for Biochemistry and Molecular Biology, 1998)
The Saccharomyces cerevisiae genome encodes 15 full-size ATPbinding cassette transporters (ABC), of whichPDR5, SNQ2, and YOR1 are known to be regulated by the transcription factors Pdr1p and Pdr3p (pleiotropic drug resistance). We have identified two new ABC transporter-encoding genes,PDR10 and PDR15, which were up-regulated by thePDR1–3 mutation. These genes, as well as four other ABC transporter-encoding genes, were deleted in order to study the properties of Yor1p. The PDR1–3 gain-of-function mutant was then used to overproduce Yor1p up to 10% of the total plasma membrane proteins. Overexpressed Yor1p was photolabeled by [γ-32P]2′,3′-O-(2,4,6-trinitrophenyl)-8-azido-ATP (K 0.5 = 45 μM) and inhibited by ATP (K D = 0.3 mM) in plasma membranes. Solubilization and partial purification on sucrose gradient allowed to detect significant Yor1p ATP hydrolysis activity (∼100 nmol of Pi·min−1·mg−1). This activity was phospholipid-dependent and sensitive to low concentrations of vanadate (I50 = 0.3 μM) and oligomycin (I50 = 8.5 μg/ml). In vivo, we observed a correlation between the amount of Yor1p in the plasma membrane and the level of resistance to oligomycin. We also demonstrated that Yor1p drives an energy-dependent, proton uncoupler-insensitive, cellular extrusion of rhodamine B. Furthermore, cells lacking both Yor1p and Pdr5p (but not Snq2p) showed increased accumulation of the fluorescent derivative of 1-myristoyl-2-[6-(NBD)aminocaproyl]phosphatidylethanolamine. Despite their different topologies, both Yor1p and Pdr5p mediated the ATP-dependent translocation of similar drugs and phospholipids across the yeast cell membrane. Both ABC transporters exhibit ATP hydrolysis in vitro, but Pdr5p ATPase activity is about 15 times higher than that of Yor1p, which may indicate mechanistic or regulatory differences between the two enzymes.